2012
DOI: 10.1159/000337340
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Drug Consumption Depending on the Time between Symptom Onset and the Diagnosis of Alzheimer’s Disease: An Analysis by the Registry of Dementias of Girona

Abstract: Aims: To describe central nervous system (CNS) drug consumption patterns depending on the time to diagnosis of Alzheimer’s disease (AD), and to check whether the cases diagnosed later are associated with greater severity and consuming more CNS drugs. Methods: Cross-sectional study using 952 cases of the Registry of Dementias of Girona. A binary logistic regression was used to detect variables associated with the use of CNS drugs depending on the time to diagnosis. Results: CNS drugs were consumed by 95.8% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Antipsychotics are often used to treat neuropsychiatric symptoms, although these drugs should be prescribed restrictively [19]. Accordingly, our data showed that institutionalized dementia patients were more likely to use antipsychotics [41,42], after adjustment for age, sex, living alone, MMSE score, overall co-morbidity and dementia disorder. There have been concerns about a possible over-prescribing of these drugs in institutions and a large variation between nursing homes has been observed [43].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Antipsychotics are often used to treat neuropsychiatric symptoms, although these drugs should be prescribed restrictively [19]. Accordingly, our data showed that institutionalized dementia patients were more likely to use antipsychotics [41,42], after adjustment for age, sex, living alone, MMSE score, overall co-morbidity and dementia disorder. There have been concerns about a possible over-prescribing of these drugs in institutions and a large variation between nursing homes has been observed [43].…”
Section: Discussionmentioning
confidence: 73%
“…Frail elderly people are sensitive to the adverse effects of these drugs, which can even cause increased mortality in this vulnerable group [20,21]. The overall use of antipsychotics in patients with AD in this study was quite low (4-5%) [41], probably due to the mild stage of disease, but maybe also because of an increased awareness of restrictive prescribing of these drugs. DLB was strongly associated with the use of antipsychotics.…”
Section: Discussionmentioning
confidence: 95%
“…Psychotropic medication use may reflect a failure to identify AD in the prodromal stages. This was the conclusion of Calvó-Perxas et al (2012) who reported that the time from symptom onset to AD diagnosis was associated with the probability of antipsychotic use. In our study, the odds of using antipsychotics over the three-year follow-up was 100% higher in persons with mild AD at baseline compared to those with very mild AD, although this result was not statistically significant.…”
Section: Daily Functioning and Disease Severitymentioning
confidence: 68%
“…An adequate management of BPSD still represents a major challenge since, on the one hand, no treatment is currently approved for this indication and, on the other, several harmful side effects significantly limit the use of available drugs, especially neuroleptics. Conventional and atypical neuroleptics, in fact, are those most commonly used, albeit they are employed off-label [1,2], and several reports and FDA warnings indicate increased mortality and an increased rate of cerebrovascular accidents, besides prolongation of the QT interval with increased risk of torsade de pointes [3]. In order to sort out reliable data on the actual risks for demented patients, some authors have recently introduced the concept of chlorpromazine or haloperidol equivalents (CE and HE, respectively, at 100 mg and 2 mg), allowing a comparison between different drugs and doses [4].…”
Section: Tablementioning
confidence: 99%